THE EFFECTIVENESS OF HUSBAND’S SUPPORT AND THE USE OF AUDIO VISUALS IN HEALTH EDUCATION TO IMPROVE PREGNANT WOMEN’S KNOWLEDGE ABOUT PERINEAL MASSAGE IN PREPARATION FOR CHILDBIRTH - Resina, selma; Damiti, Sukmawati A; Simanungkalit, Happy Marthalena; Mawaddah, Sofia (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Efforts to increase pregnant women’s knowledge about preventing ruptures include providing health education. To minimize the incidence of perineal rupture, namely by perineal massage. To determine the effect of health education using audio-visual media on husbands’ knowledge and support for third-trimester pregnant women regarding perineal massage. Pre-Experimental type of research with a one-group pretest and posttest design. The sample of this research was pregnant women in the third trimester in the Kalampangan Health Center working area, Palangka Raya City, totaling 39 respondents who met the inclusion criteria. Obtained from data analysis using the Paired sample t-test, the sig value of knowledge and husbands’ support is <0.0001. there is an influence of health education using audio-visual media on husbands’ knowledge and support for pregnant women in the third trimester.